KEPEMIMPINAN KEPALA SEKOLAH MENENGAH PERTAMA NEGERI 18 BENGKULU SELATAN - Erma Erma; Rohiat Rohiat; Manap Somantri (Manajer Pendididikan, 2017)
The objectives of this research was to determine the extent of the principal in carrying out the leaderships function, whether in academic or non academic, as an achievement which given from the principal of Junior Hight Schoul 18 South Bengkulu. The method used in this research is descriptive qualitative. The techniques of collecting the data in this research were used interview, observation, and documentation. The data was analyzed by elaborating data, displaying data, and making conclusions. Based on this research known that the principal have a honest personality, confident, responsible, willing to take risks, has a stabile emotion and competent to be exemplary; the principal has the knowledge of the educator and education, capable in developing vision and mission of the school, capable in making internal and external decisions, has good communication, democratic act, and work to improve teaching and learning quality.